Families in the Pandemic Between Challenges and Opportunities: An Empirical Study of Parents with Preschool and School-Age Children - Balenzano, Caterina; Moro, Giuseppe; Girardi, Sabrina (Italian Sociological Review, 2020)
The study explored the effects of social isolation from lockdown on Italian families in terms of work-family balance, family functioning and parenting. 104 parents (80.8% mothers) with at least one child aged from 2 to 14 years participated in the study. An ad-hoc scale explored work-family balance; Family Environment Scale and Perceived collective family efficacy scale examined respectively parents’ perceived quality of family relationships and beliefs in family’s efficacy; one single question and an ad-hoc scale measured respectively parenting stress and positive parenting. Our findings evidenced an increase of parenting stress due to the social isolation and the persistency of gender inequalities in not-paid work division causing a penalty for mothers. Nevertheless, during the lockdown, families rediscovered the values of being together inside the house, improving both their cohesion and expressiveness and their positive parenting. Overall, the study shows that Italian families have been resilient and not overwhelmed by family stress, being able to adjust to cope with lifestyle changes. However, the social changes caused by the emergency requires to plan adequate policies to support especially dual-earner families with younger children in these times, both to reduce parenting stress and to avoid that work-family balance difficulties and gender gap will be exacerbated, increasing the risk to relegating women to the domestic sphere during the next phases of this pandemic.